Servant Leadership Style "Implementation of Servant Leadership at Starbucks Corporation (Starbucks Coffee Company)" - Umah, Fadilatul; Yudha F, M.Arie; Nufal, Antoni Ahmad; Purnomo, Intan; Anshori, Mochammad Isa (Formosa Journal of Applied Sciences, 2024)
This research aims to explain the concept of servant leadership and illustrate how this approach can build a sustainable organization and have a positive impact. The research method used is literature study by examining academic articles, journals, books and other relevant sources. The purpose of this article is to find out the servant leadership style at Starbucks, as the largest coffee company. The results of the analysis show that servant leadership emphasizes the importance of creating a wider positive impact on society and the environment. Servant leaders consider the social, economic, and environmental implications of their decisions and actions. Servant leadership can help organizations respond with flexibility to changes that occur in a dynamic business environment.